Transformations in trade politics participatory trade politics in West Africa - Trommer, Silke (Routledge global institutions series, 2014)
This title expands the current boundaries of the political economy of trade beyond their focus on public and corporate actors and offers a scholarly analysis of existing and potential transformations in trade policy-making that transcend exclusive or consultative mechanisms for other social agents.